Worldwide CO2-Emissions Reached New Record High - Hans-Joachim Ziesing (Weekly Report, 2005)
Worldwide climate protection suffered another serious set-back last year. According to preliminary estimates, energy-induced emissions of carbon dioxide (CO2) - the most important greenhouse gas by far - increased by approx. 4.5% on a worldwide basis in 2004 in comparison to the previous year; compared to 1990, the increase amounted to more than one fourth. For the total greenhouse gas emissions, only information on those countries committing to emission limitation or reduction according to the Kyoto Protocol is available (Annex B countries without USA and Australia). In those countries, greenhouse gas emissions rose by an estimated 1% in the past year. In comparison to the base year 1990, in 2004 they were lower by almost 15%. This was basically a consequence of the drastic emission reduction in the so-called transformation countries (Economies in Transition) in Central and Eastern Europe (1990 to 2004: 35%); however, starting in 1998, a considerable emission increase occurred again in those countries (1998 to 2004: an increase of approx. 10%). All things considered, a measurable success in international climate protection policy is still missing _ instead of the targeted reduction, greenhouse gas emissions continued to rise in most of the countries. Upon the Kyoto Protocol becoming effective as of February 2005, those countries that ratified the Protocol now have the binding obligation to reach the promised emission target by the commitment period 2008/2012. For the majority of the countries, this will only be possible with materially intensified climate protection measures within the relatively short remaining time. In EU countries, emissions trading can make a significant contribution. However, a prerequisite therefore is the corresponding specification in the allocation plans still to be prepared for the commitment period 2008/2012.
Keywords: 330